What Determines Lean Manufacturing Implementation? A CB-SEM Model - Tan Ching Ng; Morteza Ghobakhloo (Economies, 2018)
This research aims to ascertain the determinants of effective Lean Manufacturing (LM). In this research, Covariance-based Structural Equation Modeling (CB-SEM) analysis will be used in order to analyze the determinants. Through CB-SEM analysis, the significant key determinants can be determined and the direct relationships among determinants can be analyzed. Thus, the findings of this research can act as guidelines for achievement of LM effectiveness, not only providing necessary steps for successful implementation of lean, but also helping lean companies to achieve higher level of lean cost and time savings.